The Role of Leadership in the Development of Public Organizations - Eden Komarudin Soeardi; Rizky Ilhami; Willya Achmad (Journal of Governance, 2022)
An organization's success is directly proportional to the quality of its leadership. When it comes to adapting to new circumstances and staying on top of advancements in an organization, particularly one that deals with the public or is run by the government, the position of leader is essential. Leaders in a company play an essential role in attempts to improve the quality of service, beginning with management, expanding the resources of the apparatus that delivers services, and utilizing technology. These are the three pillars of the improvement process. The purpose of this research is to investigate the role that leadership plays in the evolution of public organizations. This investigation takes a qualitative approach and makes use of descriptive research tools. According to the findings of the study, a leader is more likely to be successful in developing a public organization if he or she is able to motivate subordinates, is competent in both skills and emotions, and upholds the professional ethics that guide the leader's profession.